2022
DOI: 10.1371/journal.pone.0267305
|View full text |Cite
|
Sign up to set email alerts
|

Instruments used to measure knowledge and attitudes of healthcare professionals towards antibiotic use for the treatment of urinary tract infections: A systematic review

Abstract: Background Urinary tract infections (UTIs) are the second most common condition (after upper respiratory tract infections) for which adults receive antibiotics, and this prevalence may contribute to antibiotic resistance. Knowledge and attitudes have been identified as potential determinants of antibiotic prescribing behaviour among healthcare professionals in the treatment and management of UTIs. An instrument that captures prescribers’ baseline knowledge of and attitudes towards antibiotic prescribing for UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…The current review extends a review already published by Mwape et al (2022). In the previous review, Mwape et al (2022) focused on the psychometric properties of existing instruments that measure the knowledge and attitudes of health care professionals towards antibiotic use for treating UTIs.…”
Section: Statement Of Contributionmentioning
confidence: 85%
See 2 more Smart Citations
“…The current review extends a review already published by Mwape et al (2022). In the previous review, Mwape et al (2022) focused on the psychometric properties of existing instruments that measure the knowledge and attitudes of health care professionals towards antibiotic use for treating UTIs.…”
Section: Statement Of Contributionmentioning
confidence: 85%
“…The current review extends a review already published by Mwape et al (2022). In the previous review, Mwape et al (2022) focused on the psychometric properties of existing instruments that measure the knowledge and attitudes of health care professionals towards antibiotic use for treating UTIs. The previous review neither report information about the levels of knowledge and attitudes found in the studies retrieved, nor the item types used to conduct those assessments.…”
Section: Statement Of Contributionmentioning
confidence: 85%
See 1 more Smart Citation
“…Even so, convenience sampling was acceptable in such studies (Chen et al, 2023;Del Ponte et al, 2022;Shyu et al, 2018). Third, criterion validity of the two scales were not tested as there are no gold standard instrument existed to assess knowledge according to Mwape et al (2022) and in view of the limitations of the current instruments. Additionally, the retest reliability of the scale has not been examined, since we provided health education to the older people after the survey was complete, which might affect the retest reliability.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…According to the model by Teixeira Rodrigues et al, 16 the attitude can be broken down into six factors: complacency, fear, ignorance, indifference, responsibility and confidence. Mwape et al 17 proposed an umbrella model that merges the aforementioned models, and it applies specifically to UTIs, as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%